Genetic variability and heritability estimates among nutritional traits of groundnut breeding lines - Richard Adu Amoah; James Yaw Asibuo; Richard Akromah; Kwabena Asare Bediako; Maxwell Lamptey; Collins Yeboah Osei; Samuel Awuah; Richard Boampong (Academia Biology)
Proximate and mineral composition are noted to be important parameters that determines the nutritional quality of groundnut products. However, low genetic variability has been a major bottleneck in genetic enhancement of these characters in breeding varieties. Hence this study was conducted to determine the level of genetic diversity of the proximate and mineral composition in advance breeding lines and varieties of groundnut. The trial consisted of 12 advance breeding lines and 7 varieties which were evaluated in a randomized complete block design (RCBD) in three (3) replications at CSIR-Crop Research Institute, Fumesua, Ghana. The results showed significant genotypic effect recorded for all the traits except oil, moisture, ash and protein. The mean values recorded among the genotype were oil 47.9%, protein 21.06%, carbohydrate 19.47%, fibre 4.22%, moisture 4.79%, ash 2.8%. Whiles mineral concentration analysis revealed that the mean estimates for the genotypes were potassium (K) 1190.37(mg/100g), phosphorus (P) 280.77 (mg/100g), calcium (Ca) 222.92 (mg/100g), magnesium (Mg) 202.00 (mg/100g), iron (Fe) 1.97 (mg/100g), zinc (Zn) 2.11 (mg/100g), sodium (Na) 12.63 (mg/100g). Breeding lines Adepa × Numex 01, Yenyawoso × Numex 02, Yenyawoso × Numex 01 and Adepa Numex 02 showed more promising for protein, fat, potassium and iron. Hence, they can be utilized for selection for breeding purposes. Nonetheless, high heritability accompanied by high genetic advance as percent of mean for zinc (Zn) and iron (Fe), indicated that the heritability of these traits is due to additive gene effect and selection for such traits may be effective and rewarding.